Libraries + IRW = Big Read Success! - Coates, Jan (Maine Policy Review, 2013)
Jan Coates presents a case study of how Island Readers and Writers collaborated with local libraries in the Mt. Desert Island (Maine) area to encourage reading and community engagement through two "Big Read” events.
Keywords: Maine; libraries; reading; community engagement